Cu Migration and its Impact on the Metastable Behavior of CdTe Solar Cells. Issue 1771 (2015) - Guo, Da; Akis, Richard; Brinkman, Daniel; Moore, Andrew; Fang, Tian; Sankin, Igor; Ringhofer, Christian; Vasileska, Dragica
ABSTRACT: In this work, we report on development of one-dimensional reaction-diffusion simulator needed to understand the kinetics of Cu-related metastabilities observed in CdTe PV devices. Evolution of intrinsic and Cu-related defects in CdTe solar cells has been studied in time-space domain self-consistently with free carrier transport. Resulting device performance was simulated as a function of stress time, thus showing pronounced effect that the evolution of associated acceptor and donor states can cause on device characteristics. Although 1D simulation has intrinsic limitations when applied to poly-crystalline films, the results presented confirm the validity and the potential of the approach presented in better understanding of the performance and metastabilities of CdTe photovoltaic devices.